Cancer Epidemiology and Prevention in Children and Adolescents – View Thesis - Lewandowska, Anna (International Journal of Pediatrics and Child Health, 2013)
Growing up in the world of globalization and changes in families’ structure generate noticeable health and psychosocial well-being threats in children and adolescents [167]. Civilization development, as well as technical, economic, and industrial progress, despite obvious positive changes they bring, have also become the reason for disorder of internal homeostasis of an organism due to continuous influence of various harmful external factors, and their existence is connected to civilization development. Due to civilization development human being in every stage of their life, from conception to adulthood, is exposed to carcinogenic factors that are responsible for malignant transformation of a cell that is formation of tumours. Technological advance, modern methods of research, primary and secondary prophylaxis, do not stop the problem of growing tumors. Every year in Poland about 1,300 new cases of cancer appear in Poland, which are the cause of death in children, or cause permanent disability and mental strain. Today we know that the diseases of civilisation, including cancers, are curable, but the key to success is to reduce the risk of these diseases and early diagnosis. Statistics show that in the developed countries the detection of cancer in children happens already in stage I and II of the disease, while in Poland, the diagnosis is made most often in stage III and IV, which gives a much lower chance of recovery. Therefore, the question appears: what action needs to be taken to change the current situation. Prevention, or in other words the reduction of occurance of such diseases by reducing the exposure to harmful factors, is very important, but so is early diagnosis, which includes screening and the increase of children's knowledge about health risks and healthy behaviors.